The Effective Moral Education on Early Childhood As an Effort Against Immoral Culture - Zulfani Sesmiarni (LPPM Universitas Pahlawan Tuanku Tambusai, 2019)
Basically, effective moral education which concerns with affective aspect can prevent the immoral culture that occur around the community. The Education implemented in domiciliary, school, and society can influence and form ones morality. The immoral culture, nowadays, that has spreaded in young generation, reflects to peoples live. The parents, the expert of education and those who concern with religion and social skill, lately, are confused with teenagers behaviour. They are uncontrollable, naughty, stubborn, trouble maker, immoral, brawls, drug, even piracy, rape, murder, and other abandoned acts. These problems need to be solved immediately. While theoritical moral education is not enough to overcome these such actions, but the teenagers require model as sample in their real life. This research in the form of content analysis is a series of activities relating to library data collection methods. A series of activities relating to the method of collecting library data, reading and recording and processing research materials. Data analysis in this study was carried out through a process of systematically searching and compiling data obtained. It reflects moral education is very crucial to be encouraged especially for early childhood